Antiviral aerosol composition, coating film and article

By adding vinylpyrrolidone unit polymer and alcohol-based solvent to the copper-doped silica aerosol, and using ball milling treatment technology, the blockage problem during the coating process is solved, and copper-doped silica is realized on the surface of the article Maintain excellent antiviral performance and stability, suitable for protection of various viruses.

CN119183470APending Publication Date: 2024-12-24TOYO SEIKAN GRP HLDG LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380040100.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-06-06
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing copper-doped silica aerosol compositions tend to clog the nozzle during the coating process and are difficult to maintain excellent antiviral properties and stability.

Method used

Using polymers containing vinyl pyrrolidone units as resin components, combined with alcohol-based solvents and sprayers, the uniform dispersion and high adhesion of copper-doped silica are ensured through ball milling treatment technology, forming a coating film that does not clog the nozzle, and Maintain excellent antiviral properties on the surface of the article.

Benefits of technology

The coating film with copper-doped silica firmly maintained on the surface of the article is achieved, with high stability and excellent antiviral properties, is effective against both enveloped and non-encapsulated viruses, and does not clog the nozzle during the injection process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130663010000191
    Figure BDA0005130663010000191
  • Figure BDA0005130663010000201
    Figure BDA0005130663010000201
  • Figure BDA0005130663010000211
    Figure BDA0005130663010000211
Patent Text Reader

Abstract

The present invention addresses the problem of providing: an antiviral aerosol composition which is capable of forming a coating film that exhibits excellent antiviral properties in copper-doped silica and is firmly held on the surface of an article, has high stability, and is capable of applying an aerosol without clogging a nozzle; and a coating film formed from the antiviral aerosol composition and an article having the coating film. The antiviral aerosol composition according to the present invention, which is a solution therefor, contains (1) a copper-doped silica; (2) a polymer containing a vinyl pyrrolidone unit; (3) an alcohol solvent or a mixed solvent of an alcohol solvent and water; and (4) a propellant. The coating film of the present invention is formed from the antiviral aerosol composition of the present invention. The article of the present invention has the coating film of the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an antiviral aerosol composition, a coating film and an article. Background Art

[0002] As is known to all, in recent years, since the emergence of new influenza viruses and coronaviruses that cause severe symptoms due to infection, people have become increasingly concerned about antiviral preparations for viral infection countermeasures. According to the structure, viruses are roughly divided into viruses with an envelope composed of lipids or glycoproteins (enveloped viruses) and viruses without an envelope (non-enveloped viruses). Influenza virus is a representative example of enveloped viruses, and norovirus is a representative example of non-enveloped viruses. Compared with enveloped viruses, non-enveloped viruses can be said to have stronger resistance to alcohol and heat, etc., and are more contagious. Therefore, people have invested a lot of energy in the research and development of antiviral preparations that show excellent antiviral effects not only on enveloped viruses but also on non-enveloped viruses. Regarding this type of antiviral preparation that shows excellent antiviral effects not only on enveloped viruses but also on non-enveloped viruses, the inventors of the present invention have also proposed a copper-doped silica inorganic antiviral preparation in Patent Document 1.

[0003] The inorganic antiviral preparation proposed by the present inventors in Patent Document 1 can be used as a material for imparting antiviral properties to various objects around us, but as a method of utilizing it, in the case of using copper-doped silica in combination with an aerosol composition and applying the aerosol to the surface of an object, the coating formed by the aerosol composition containing copper-doped silica is required not only to enable the copper-doped silica to exhibit excellent antiviral properties and to be firmly maintained on the surface of the object, but also to have a high stability of the aerosol composition containing copper-doped silica so that the aerosol can be applied without clogging the nozzle.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-175741 Summary of the invention

[0007] Problems to be solved by the invention

[0008] Therefore, the object of the present invention is to provide an antiviral aerosol composition that can form a coating film in which copper-doped silica exhibits excellent antiviral performance and is firmly maintained on the surface of an article, has high stability, and can be coated with an aerosol without clogging the nozzle, as well as a coating film formed by the antiviral aerosol composition and an article having the coating film.

[0009] Technical solutions to solve problems

[0010] The present inventors conducted in-depth research in view of the above aspects and found that: in the process of manufacturing an aerosol composition containing copper-doped silica, when a polymer containing vinyl pyrrolidone units is used as a resin component (film-forming agent), the coating film formed by the aerosol composition is a product in which the copper-doped silica exhibits excellent antiviral properties and is firmly maintained on the surface of an article, and the aerosol composition has high stability and can be coated with an aerosol without clogging the nozzle.

[0011] The antiviral aerosol composition of the present invention completed based on the above-mentioned knowledge is as described in claim 1, comprising

[0012] (1) Copper-doped silicon dioxide;

[0013] (2) Polymers containing vinyl pyrrolidone units;

[0014] (3) an alcohol solvent or a mixed solvent of an alcohol solvent and water; and

[0015] (4) Propellant.

[0016] In addition, the antiviral aerosol composition according to claim 2 is the antiviral aerosol composition according to claim 1, wherein the silicon dioxide is further doped with aluminum.

[0017] Furthermore, the antiviral aerosol composition according to claim 3 is the antiviral aerosol composition according to claim 1, wherein the silica is porous silica.

[0018] Furthermore, the antiviral aerosol composition according to claim 4 is the antiviral aerosol composition according to claim 1, wherein the polymer containing the pyrrolidone unit is a copolymer of a vinyl pyrrolidone unit and a unit other than vinyl pyrrolidone.

[0019] In addition, the antiviral aerosol composition according to claim 5 is the antiviral aerosol composition according to claim 4, wherein the ratio of the vinyl pyrrolidone unit to the unit other than vinyl pyrrolidone (vinyl pyrrolidone unit: unit other than vinyl pyrrolidone) is 2:8 to 8:2.

[0020] The antiviral aerosol composition according to claim 6 is the antiviral aerosol composition according to claim 4, wherein the copolymer of the vinyl pyrrolidone unit and the unit other than vinyl pyrrolidone is a copolymer of vinyl pyrrolidone and vinyl acetate.

[0021] Furthermore, the antiviral aerosol composition according to claim 7 is the antiviral aerosol composition according to claim 1, wherein the polymer containing a pyrrolidone unit is polyvinylpyrrolidone.

[0022] Furthermore, the antiviral aerosol composition according to claim 8 is the antiviral aerosol composition according to claim 1, wherein the weight average molecular weight of the polymer containing the pyrrolidone unit is 5,000 to 1,500,000.

[0023] Furthermore, the antiviral aerosol composition according to claim 9 is the antiviral aerosol composition according to claim 1, wherein the alcohol solvent is ethanol.

[0024] In addition, the antiviral aerosol composition according to claim 10 is the antiviral aerosol composition according to claim 1, wherein the propellant is at least one selected from liquefied petroleum gas, nitrogen, carbon dioxide gas, dimethyl ether, hydrofluoroolefins, and hydrofluorocarbons.

[0025] In addition, the antiviral aerosol composition described in claim 11 is the antiviral aerosol composition described in claim 1, wherein the contents of copper-doped silica, polymer containing vinyl pyrrolidone units, alcohol solvent or a mixed solvent of an alcohol solvent and water, and propellant in the antiviral aerosol composition are respectively: the content of copper-doped silica is 0.1 to 5 weight %, the content of polymer containing vinyl pyrrolidone units is 0.1 to 5 weight %, the content of alcohol solvent or a mixed solvent of an alcohol solvent and water is 30 to 90 weight %, and the content of propellant is 5 to 65 weight %.

[0026] In addition, the antiviral aerosol composition described in claim 12 is the antiviral aerosol composition described in claim 1, wherein the weight ratio of copper-doped silica to the polymer containing vinyl pyrrolidone units (copper-doped silica: polymer containing vinyl pyrrolidone units) is 5:95 to 75:25.

[0027] In addition, the method for producing an antiviral aerosol composition of the present invention is as described in claim 13, comprising: placing (1) copper-doped silica, (2) a polymer containing a vinyl pyrrolidone unit, and (3) an alcohol solvent or a mixed solvent of an alcohol solvent and water in a processing container, and mixing a stock solution obtained by a preparation method including a ball milling process with (4) a propellant.

[0028] Furthermore, the coating film of the present invention is formed of the antiviral aerosol composition according to claim 1 as described in claim 14 .

[0029] Furthermore, the article of the present invention is as recited in claim 15 and comprises the coating film as recited in claim 14 .

[0030] Effects of the Invention

[0031] According to the present invention, there can be provided an antiviral aerosol composition which can form a coating film in which copper-doped silica exhibits excellent antiviral performance and is firmly maintained on the surface of an article, has high stability, and can be coated with an aerosol without clogging a nozzle, as well as a coating film formed by the antiviral aerosol composition and an article having the coating film. DETAILED DESCRIPTION

[0032] The antiviral aerosol composition of the present invention contains

[0033] (1) Copper-doped silicon dioxide;

[0034] (2) Polymers containing vinyl pyrrolidone units;

[0035] (3) an alcohol solvent or a mixed solvent of an alcohol solvent and water; and

[0036] (4) Propellant.

[0037] In the antiviral aerosol composition of the present invention, the copper-doped silica may be, for example, an inorganic antiviral agent described in Patent Document 1. Here, "copper-doped silica" refers to silica into which copper is introduced by chemical bonding in an inorganic network formed by siloxane bonds constituting silica. The copper-doped silica may be porous or non-porous, and there is no particular limitation on its shape.

[0038] Copper-doped silicon dioxide may also be doped with metals such as aluminum, zirconium, cobalt, manganese, and iron.

[0039] The copper content in copper-doped silica (the total amount of each metal when other metals are used in combination in addition to copper) is, for example, 0.01 to 40% by weight, preferably 0.1 to 20% by weight, and more preferably 1 to 10% by weight. If the copper content in copper-doped silica is less than 0.01% by weight, it may not be possible to obtain a sufficient antiviral effect. On the other hand, silica doped with more than 40% by weight of copper may be difficult to manufacture. When other metals are used in combination in addition to copper, the content ratio between copper and other metals can be, for example, 0.1 to 2 times the content of other metals relative to the content of copper.

[0040] When the copper-doped silica is porous, the copper-doped porous silica may be, for example, a product described in Japanese Patent Application Laid-Open No. 2020-15640 by the present inventors. The details are as follows.

[0041] Examples of porous silica include mesoporous silica in which micropores (mesopores) having a diameter of 2 to 50 nm are regularly arranged.

[0042] The specific surface area of ​​porous silica is, for example, 500 to 2000 m2 / g is preferred because durability can be maintained.

[0043] The production of copper-doped mesoporous silica can be carried out according to the following method which is known per se and is described in, for example, JP-A-2020-15640.

[0044] (Process 1)

[0045] First, a surfactant and a raw material for doping mesoporous silica with copper are dissolved in a solvent, and micelles are formed in the surfactant by stirring at a temperature of, for example, 30 to 200° C. for 0.5 to 10 hours.

[0046] The amount of the surfactant dissolved in the solvent is, for example, 10 to 400 mmol / L, preferably 50 to 150 mmol / L. Alternatively, the amount of the surfactant dissolved in the solvent is, for example, 0.01 to 5.0 mol, preferably 0.05 to 1.0 mol, relative to 1 mol of the silica raw material added in step 2 described below.

[0047] As a surfactant, any one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant can be used, preferably a cationic surfactant such as an alkyl ammonium salt. The alkyl ammonium salt is preferably an ammonium salt of an alkyl group with a carbon number of 8 or more, and considering the industrial availability, it is more preferably an ammonium salt of an alkyl group with a carbon number of 12 to 18. As a specific example of an alkyl ammonium salt, hexadecyl trimethyl ammonium chloride, cetyl trimethyl ammonium bromide, stearyl trimethyl ammonium bromide, cetyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, dodecyl trimethyl ammonium bromide, octadecyl trimethyl ammonium bromide, dodecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, didodecyl dimethyl ammonium bromide, ditetradecyl dimethyl ammonium bromide, didodecyl dimethyl ammonium chloride, and ditetradecyl dimethyl ammonium chloride can be cited. The surfactant can be used alone or in combination of two or more.

[0048] The amount of the raw materials for doping copper into mesoporous silica dissolved in the solvent (the total amount of each raw material when other metals are used in combination in addition to copper) is, for example, 0.001 to 1 mol, preferably 0.005 to 0.5 mol, and more preferably 0.01 to 0.1 mol, relative to 1 mol of the silica raw material added in the later-described step 2.

[0049] As raw materials for doping copper or other metals other than copper into mesoporous silica, for example, their nitrates, sulfates, chlorides, and oxychlorides can be used. As raw materials for doping copper, copper nitrate, copper chloride, and the like are preferably used. As raw materials for doping aluminum in addition to copper, aluminum chloride is preferably used. As raw materials for doping zirconium, zirconium oxychloride is preferably used. As raw materials for doping cobalt, cobalt nitrate is preferably used. As raw materials for doping manganese, manganese chloride is preferably used. As raw materials for doping iron, ferric chloride is preferably used. The raw materials for doping copper or other metals other than copper can be used alone or in combination of two or more.

[0050] As the solvent, for example, water can be used, or the solvent may be a mixed solvent of water and a water-soluble organic solvent represented by a polyol such as methanol, ethanol, diethylene glycol, and glycerin.

[0051] (Process 2)

[0052] Next, in the solution of the surfactant micelles obtained in step 1, a silica raw material is dissolved and stirred at room temperature, for example, until uniform, so that the silica raw material is aggregated on the micelle surface of the surfactant. The amount of silica raw material dissolved in the solution is, for example, 0.2 to 1.8 mol / L. Alternatively, when water or a mixed solvent of water and a water-soluble organic solvent is used as the solvent, it is, for example, 0.001 to 0.05 mol relative to 1 mol of water.

[0053] The silica raw material can be any material that can form an inorganic network composed of siloxane bonds constituting mesoporous silica through dehydration condensation, and there is no particular limitation. As a specific example of the silica raw material, tetraalkoxysilanes such as tetraethoxysilane, tetramethoxysilane, and tetra-n-butoxysilane and sodium silicate can be cited. Preferably, tetraalkoxysilane, more preferably tetraethoxysilane. The silica raw material can be used alone or in combination of two or more.

[0054] (Process 3)

[0055] Next, the silica raw material gathered on the surface of the surfactant micelle is dehydrated and condensed to form an inorganic network composed of siloxane bonds constituting mesoporous silica, and copper is introduced into the inorganic network through chemical bonds. The dehydration and condensation of the silica raw material can be achieved by, for example, adding an alkaline aqueous solution to the system to increase the pH value and stirring at room temperature for more than 1 hour. The addition of the alkaline aqueous solution is preferably such that the pH value immediately changes to 8 to 14 after addition, and more preferably changes to 9 to 11. As specific examples of alkaline aqueous solutions, there can be cited aqueous sodium hydroxide solution, aqueous sodium carbonate solution, and ammonia water, preferably aqueous sodium hydroxide solution. The alkaline aqueous solution can be used alone or in combination of two or more. It should be noted that the dehydration and condensation of the silica raw material can also be achieved by adding an acidic aqueous solution such as an aqueous hydrochloric acid solution to the system to lower the pH value and then stirring.

[0056] (Process 4)

[0057] Finally, the micelles of surfactant formed on the surface of the inorganic network composed of siloxane bonds constituting mesoporous silica and copper introduced through chemical bonds obtained in step 3 are filtered and recovered as precipitates, dried at a temperature of, for example, 30 to 70° C. for 10 to 48 hours, and then calcined at a temperature of 400 to 600° C. for 1 to 10 hours to obtain copper-doped mesoporous silica as the target product. The copper-doped mesoporous silica thus obtained can also be crushed to a desired particle size (for example, a median particle size of 0.01 to 100 μm) using a mixer, a grinder, etc. as needed.

[0058] It should be noted that the raw materials added into the system for doping copper into the mesoporous silica are not limited to the method of dissolving them in the solvent together with the surfactant in the above-mentioned step 1. It can be added before the step 3 in which the silica raw materials are dehydrated and condensed to form an inorganic network composed of siloxane bonds constituting the mesoporous silica. It can also be dissolved in the solution in step 2 or step 3.

[0059] In the case where the copper-doped silica is non-porous, the copper-doped non-porous silica can be manufactured using, for example, a sedimentation method which is a common method for manufacturing non-porous silica. Specifically, when the alkali metal silicate as a raw material for silica is neutralized with an inorganic acid, it can be manufactured by allowing the raw material for copper doping into the non-porous silica to coexist in the system. The raw material for doping copper into non-porous silica can be the same as the raw material for doping the above-mentioned copper into mesoporous silica. Regarding the amount of raw materials for doping copper into non-porous silica (the total amount of each raw material when other metals are used in combination in addition to copper), for example, 0.001 to 0.5 mol, preferably 0.01 to 0.1 mol, relative to 1 mol of alkali metal silicate as a raw material for silica. The alkali metal silicate used as a raw material for silica can be a conventional alkali metal silicate used for manufacturing non-porous silica by a sedimentation method. Specifically, sodium silicate, potassium silicate, etc. can be cited, and the molar ratio of silicon dioxide to alkali SiO2 / M2O (M is Na, K, etc.) is, for example, 0.5 to 4. The amount of alkali metal silicate dissolved in the solvent (water, etc.) is, for example, 0.001 to 0.05 mol relative to 1 mol of the solvent. As inorganic acids, hydrochloric acid, sulfuric acid, nitric acid, etc. can be used. Copper-doped non-porous silica can be obtained as a precipitate generated by the neutralization reaction of alkali metal silicate and inorganic acid, and its filtration, washing, drying, etc. can be carried out according to the method used when manufacturing non-porous silica by sedimentation method. If necessary, it can be finally sintered at a high temperature of more than 300°C. The specific surface area (BET specific surface area) of the copper-doped non-porous silica manufactured in this way is, for example, 0.1 to 350m 2 If necessary, the copper-doped mesoporous silica may be pulverized using a mixer or a grinder to have a desired particle size (eg, a median particle size of 0.01 to 100 μm), similar to the copper-doped mesoporous silica.

[0060] In the antiviral aerosol composition of the present invention, the polymer containing vinyl pyrrolidone units used as a resin component may be, for example, a copolymer of vinyl pyrrolidone units and units other than vinyl pyrrolidone. In this case, in order to easily form a coating film that allows copper-doped silica to exhibit excellent antiviral properties and is firmly held on the surface of an article, the ratio of vinyl pyrrolidone units to units other than vinyl pyrrolidone (vinyl pyrrolidone units: units other than vinyl pyrrolidone) is preferably 2:8 to 8:2. Specific examples of copolymers of vinyl pyrrolidone units and units other than vinyl pyrrolidone include copolymers of vinyl pyrrolidone and dimethylaminoethyl methacrylate, copolymers of vinyl pyrrolidone and methylvinyl imidazoline chloride, copolymers of vinyl pyrrolidone and dimethylaminopropionamide methacrylate, copolymers of vinyl pyrrolidone and quaternized imidazoline, copolymers of vinyl pyrrolidone and vinyl caprolactam and methylvinyl imidazolium methyl sulfate, copolymers of vinyl pyrrolidone and vinyl acetate, copolymers of vinyl pyrrolidone and eicosene, copolymers of vinyl pyrrolidone and hexadecene, copolymers of vinyl pyrrolidone and styrene, copolymers of vinyl pyrrolidone and vinyl caprolactam and dimethylaminoethyl methacrylate. In addition, the polymer containing the vinyl pyrrolidone unit may also be polyvinyl pyrrolidone. The weight average molecular weight of the polymer containing vinyl pyrrolidone units is, for example, 5,000 to 1,500,000, preferably 6,000 to 1,000,000, more preferably 7,000 to 500,000, and further preferably 8,000 to 100,000. When the weight average molecular weight of the polymer containing vinyl pyrrolidone units is too small, when the copper-doped silica is porous, the molecules will enter the micropores of the silica, and when it is expected that the performance brought by the micropores other than antiviral performance (such as deodorization, etc.) will be exhibited, it may be difficult to exhibit such performance; and when the weight average molecular weight is too large, the molecules will completely cover the surface of the silica, which may hinder the antiviral activity of the silica exhibited by adsorbing viruses. The polymer containing vinyl pyrrolidone units can be used alone or in combination of two or more.

[0061] In the antiviral aerosol composition of the present invention, the alcohol solvent may be a conventional solvent used as a component of the aerosol composition, and specific examples thereof include methanol, ethanol, and isopropanol. The alcohol solvent may be used alone or in combination of two or more. When a mixed solvent of an alcohol solvent and water is used, the weight ratio of the alcohol solvent to water (alcohol solvent: water) is, for example, 1:5 to 100:1.

[0062] In the antiviral aerosol composition of the present invention, the propellant may be a conventional propellant used for aerosol composition components, and specific examples thereof include liquefied petroleum gas, nitrogen, carbon dioxide, dimethyl ether, hydrofluoroolefins, and hydrofluorocarbons. The propellant may be used alone or in combination of two or more.

[0063] The contents of copper-doped silica, polymer containing vinyl pyrrolidone units, alcoholic solvent or mixed solvent of alcoholic solvent and water, and propellant in the antiviral aerosol composition of the present invention are, for example, 0.1-5% by weight of copper-doped silica, 0.1-5% by weight of polymer containing vinyl pyrrolidone units, 30-90% by weight of alcoholic solvent or mixed solvent of alcoholic solvent and water, and 5-65% by weight of propellant, preferably 0.2-2% by weight of copper-doped silica, 0.2-2% by weight of polymer containing vinyl pyrrolidone units, 45-70% by weight of alcoholic solvent or mixed solvent of alcoholic solvent and water, and 25-50% by weight of propellant. The antiviral aerosol composition of the present invention may contain pigments, fragrances, dispersants, defoamers, leveling agents, lubricants, mildew inhibitors, preservatives, waxes, etc., which are generally used as components of aerosol compositions. In the case where these components are mixed, the content of the alcoholic solvent or the mixed solvent of the alcoholic solvent and water will be reduced accordingly by the content of this part of the components. In addition, when the antiviral aerosol composition of the present invention is manufactured, when the copper-doped silica is provided in the form of a slurry suspended in a dispersion medium different from the alcoholic solvent or the mixed solvent of the alcoholic solvent and water used in the antiviral aerosol composition of the present invention, or the polymer containing the vinyl pyrrolidone unit is provided in the form of a solution dissolved in a solvent different from the alcoholic solvent or the mixed solvent of the alcoholic solvent and water used in the antiviral aerosol composition of the present invention, the antiviral aerosol composition of the present invention may contain such a dispersion medium or solvent, in which case, the content of the alcoholic solvent or the mixed solvent of the alcoholic solvent and water will be reduced accordingly by the content of this part of the components.

[0064] The weight ratio of copper-doped silica to the polymer containing vinyl pyrrolidone units in the antiviral aerosol composition of the present invention (copper-doped silica: polymer containing vinyl pyrrolidone units) is preferably 5:95 to 75:25, more preferably 15:85 to 70:30, and further preferably 25:75 to 65:35. If the ratio of copper-doped silica is too low, it may be difficult to form a copper-doped silica coating film that exhibits excellent antiviral performance; on the other hand, if the ratio of the polymer containing vinyl pyrrolidone units is too low, it may be difficult to form a coating film that is firmly held on the surface of an article.

[0065] The antiviral aerosol composition of the present invention can be manufactured according to a conventional method for manufacturing aerosol compositions, for example, by mixing a stock solution prepared by mixing copper-doped silica, a polymer containing a vinyl pyrrolidone unit, an alcoholic solvent or a mixed solvent of an alcoholic solvent and water at required contents, adjusting the temperature as needed, and a propellant.

[0066] It is preferred that the copper-doped silica, the polymer containing vinyl pyrrolidone units, the alcoholic solvent or the mixed solvent of the alcoholic solvent and water used to prepare the stock solution are mixed by a ball mill to process these raw materials. By treating the copper-doped silica, the polymer containing vinyl pyrrolidone units, the alcoholic solvent or the mixed solvent of the alcoholic solvent and water with a ball mill, the copper-doped silica can be obtained in the alcoholic solvent or the mixed solvent of the alcoholic solvent and water in which the polymer containing vinyl pyrrolidone units is uniformly dissolved without agglomeration. The copper-doped silica carried is uniformly dispersed without agglomeration in the formed coating film, so that it can be prevented from falling off from the coating film, and although copper-doped silica coexists at the same time, the polymer containing vinyl pyrrolidone units achieves high adhesion to the surface of the article, and it is easy to form a film that copper-doped silica exhibits excellent antiviral performance and is firmly maintained on the surface of the article. Moreover, it is easy to improve the stability of the antiviral aerosol composition of the present invention and apply the aerosol without clogging the nozzle.

[0067] The ball milling treatment can be achieved by placing copper-doped silica, a polymer containing a vinyl pyrrolidone unit, an alcoholic solvent or a mixed solvent of an alcoholic solvent and water together with grinding balls (medium) used in a ball mill in a treatment container, assembling the treatment container containing these raw materials on a ball mill stand and rotating it (the number of revolutions is selected in the range of, for example, 15 to 2000 rpm). The ball milling treatment time is, for example, 1 to 50 hours, preferably 6 to 30 hours. The grinding balls used in the ball mill (for example The number of alumina balls or zirconium oxide balls) is preferably such that the weight of the grinding balls is 1 to 5 times the total weight of the dispersion medium and the solvent in which the copper-doped silica, the polymer containing vinyl pyrrolidone units, the alcoholic solvent or the mixed solvent of the alcoholic solvent and water are dissolved or dispersed, and other components are added as needed, when the copper-doped silica is provided in the form of a slurry suspended in a dispersion medium that is different from the alcoholic solvent or the mixed solvent of the alcoholic solvent and water used in the antiviral aerosol composition of the present invention, and the polymer containing vinyl pyrrolidone units is provided in the form of a solution dissolved in a solvent that is different from the alcoholic solvent or the mixed solvent of the alcoholic solvent and water used in the antiviral aerosol composition of the present invention. The alcoholic solvent or the mixed solvent of the alcoholic solvent and water contained in the processing container may be a part of the content of the antiviral aerosol composition of the present invention. In this case, after the ball milling treatment, the alcoholic solvent or the mixed solvent of the alcoholic solvent and water may be added to reach the content in the antiviral aerosol composition of the present invention.

[0068] The antiviral aerosol composition of the present invention can be used for fiber products, non-woven products, leather products, building materials, wood, glass, plastics, films, ceramics, paper, pulp, stationery, toys, containers, container caps, pouring tools, nozzles and other items around us for the purpose of imparting antiviral properties. The antiviral aerosol composition of the present invention can be applied to the surface of the article by, for example, filling the antiviral aerosol composition of the present invention into a spray can and applying the aerosol on the surface of the article. By applying the antiviral aerosol composition of the present invention on the surface of the article and then drying it naturally or heating it to dry it, it is possible to form a coating film in which copper-doped silica exhibits excellent antiviral properties and is firmly maintained on the surface of the article.

[0069] In the coating formed by the antiviral aerosol composition of the present invention, the copper-doped silica contained in the coating not only exhibits excellent antiviral effects on enveloped viruses, but also exhibits excellent antiviral effects on non-enveloped viruses. Therefore, the type of virus as the object of the antiviral effect is not limited, and various pathogenic viruses can be used as the object, for example, as enveloped viruses, influenza A virus, influenza B virus, influenza C virus, parainfluenza virus, mumps virus (mumps virus), measles virus, human metapneumovirus, RS virus, Nipah virus, Hendra virus, yellow fever virus, dengue virus, Japanese encephalitis virus, West Nile virus, hepatitis B virus, hepatitis C virus, hepatitis D virus, Eastern equine encephalitis virus, Western equine encephalitis virus, rubella virus, Lassa virus, Junin virus, Machupo virus, South American hemorrhagic fever virus, Sabia virus, Crimean-Congo hemorrhagic fever virus, sandfly fever virus, Hanta virus, Sinnubai virus, rabies virus, The targets include Ebola virus, Marburg virus, bat lyssavirus, human T-cell leukemia virus, human immunodeficiency virus, human coronavirus, SARS coronavirus, SARS-CoV-2 virus (COVID-19 virus), herpes virus, varicella-zoster virus, Epstein-Barr virus, cytomegalovirus, smallpox virus, monkeypox virus, vaccinia virus, molluscum pox virus, parapox virus, and Ornheal virus. Non-enveloped viruses include rhinovirus, poliovirus, foot-and-mouth disease virus, rotavirus, norovirus, enterovirus, hepatovirus, astrovirus, sapovirus, hepatitis A virus, hepatitis E virus, human parvovirus, polyomavirus, human papillomavirus, adenovirus, and coxsackievirus.

[0070] In addition, the copper-doped silica contained in the antiviral aerosol composition of the present invention can exhibit excellent antiviral effects even during the period from applying the antiviral aerosol composition of the present invention to the surface of the article until the coating film is formed. During this period, the alcohol solvent or the mixed solvent of the alcohol solvent and water contained in the antiviral aerosol composition of the present invention also exhibits an antiviral effect.

[0071] Example

[0072] The present invention will be described in detail below with reference to Examples, but the present invention is not to be construed as being limited to the following descriptions.

[0073] Manufacturing Reference Example 1: Manufacturing of Mesoporous Silica Doped with Copper and Aluminum

[0074] Hexadecyltrimethylammonium chloride as a surfactant, copper chloride as a raw material for doping copper into mesoporous silica, and aluminum chloride as a raw material for doping aluminum into mesoporous silica were dissolved in water as a solvent, stirred at 100°C for 1 hour, cooled to room temperature, and then tetraethoxysilane as a raw material for silica was further dissolved and stirred until uniform. Next, sodium hydroxide aqueous solution as an alkaline aqueous solution was added to the reaction solution in such a way that the pH value immediately after addition was 9, and then stirred at room temperature for 20 hours. The generated precipitate was filtered and recovered, dried at 50°C for 24 hours, and then calcined at 570°C for 5 hours, thereby obtaining the target product, mesoporous silica doped with copper and aluminum, in the form of a slightly bluish white powder.

[0075] It should be noted that the amounts of hexadecyltrimethylammonium chloride as a surfactant, copper chloride as a raw material for doping copper into mesoporous silica, aluminum chloride as a raw material for doping aluminum into mesoporous silica, and water as a solvent relative to 1 mol of tetraethoxysilane as a raw material of silica are as follows:

[0076] Hexadecyltrimethylammonium chloride: 0.225 mol

[0077] Copper chloride: 0.0204 mol

[0078] Aluminum chloride: 0.0482 mol

[0079] Water: 125 mol

[0080] In order to prepare the sodium hydroxide aqueous solution as the alkaline aqueous solution, 0.195 mol of sodium hydroxide was used per 1 mol of tetraethoxysilane as the silica raw material.

[0081] The specific surface area of ​​the mesoporous silica doped with copper and aluminum obtained by the above method is 1100 m 2 / g, the micropore diameter is about 2.5nm (using MicrotracBEL company BELSORP MAX II type, multi-point method to measure the nitrogen adsorption isotherm at liquid nitrogen temperature, calculated by BJH). In addition, about 50mg of mesoporous silica doped with copper and aluminum was accurately weighed and dissolved in 4mL of hydrochloric acid, and then the concentration of copper and aluminum in the hydrochloric acid solution was measured by inductively coupled plasma emission spectrometer (iCAP PRO XP ICP-OES made by Thermo Fisher Scientific, the same below). The copper content and aluminum content in the mesoporous silica doped with copper and aluminum were calculated based on the measurement results. The result is that the copper content is 2.09% by weight and the aluminum content is 2.00% by weight. The fact that copper and aluminum are doped in mesoporous silica can be confirmed by X-ray photoelectron spectrometer (K-Alpha Surface Analysis made by ThermoFisher Scientific, the same below) and transmission electron microscope (JEM 2010 made by JEOL, the same below).

[0082] Production Example 1: Production of the antiviral aerosol composition of the present invention (Part 1)

[0083] (Process 1)

[0084] In a 2L iBoy PP wide-mouth bottle, 140 g of the mesoporous silica doped with copper and aluminum obtained in Preparation Reference Example 1, 560 g of ethanol, 1760 g of alumina balls are mounted on a ball mill stand at room temperature, treated at a rotation speed of 250 rpm for 1 hour, and then treated at a rotation speed of 450 rpm for 9 hours. The alumina balls are then removed to obtain an ethanol slurry with a median particle size of about 0.6 μm and a mesoporous silica content of 20 wt% doped with copper and aluminum (the median particle size is measured by a laser diffraction particle size distribution measuring device (SALD-3100 manufactured by Shimadzu Corporation) and the same below).

[0085] (Process 2)

[0086] 35 g of a powder of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630, manufactured by Ashland, the ratio of vinyl pyrrolidone unit to vinyl acetate unit is 6:4, weight average molecular weight (nominal value) 51,000, the same below) and 490 g of ethanol were added to a 2 L iBoy PP wide-mouth bottle. After the powder of the copolymer of vinyl pyrrolidone and vinyl acetate was dissolved in ethanol, 175 g of an ethanol slurry of mesoporous silica doped with copper and aluminum having a median particle size of about 0.6 μm and a content of 20 wt % obtained in step 1 was added. 1760g of alumina balls were assembled on a ball mill stand at room temperature and processed at a speed of 500rpm for 9 hours, and then the alumina balls were removed to obtain an antiviral coating composition with a median particle size of about 0.5μm, a content of 5% by weight of mesoporous silica doped with copper and aluminum, a content of 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90% by weight of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution with a median particle size of about 0.5μm, a content of 1% by weight of mesoporous silica doped with copper and aluminum, a content of 1% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 98% by weight of ethanol.

[0087] (Process 3)

[0088] The stock liquid obtained in step 2 and liquefied petroleum gas (vapor pressure at 20°C: 0.29 MPa, the same below) as a propellant are filled into an aerosol can at a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention having a median particle size of about 0.5 μm, a content of mesoporous silica doped with copper and aluminum of 0.6 weight%, a content of a copolymer of vinyl pyrrolidone and vinyl acetate of 0.6 weight%, an ethanol content of 58.8 weight%, and a liquefied petroleum gas content of 40.0 weight%.

[0089] Production Example 2: Production of the antiviral aerosol composition of the present invention (Part 2)

[0090] In a 2L iBoy PP wide-mouth bottle, 35 g of the mesoporous silica doped with copper and aluminum obtained in Preparation Reference Example 1, 315 g of ethanol, 350 g of a 10 wt % ethanol solution of a powder of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630), 1700g of alumina balls were assembled on a ball mill stand at room temperature and processed at a speed of 900rpm for 24 hours, and then the alumina balls were removed to obtain an antiviral coating composition having a median particle size of about 0.5μm, a content of 5% by weight of mesoporous silica doped with copper and aluminum, a content of 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90% by weight of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution having a median particle size of about 0.5μm, a content of 1% by weight of mesoporous silica doped with copper and aluminum, a content of 1% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 98% by weight of ethanol. The obtained raw liquid and liquefied petroleum gas as a propellant are filled into an aerosol can in a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention, which contains 0.6 weight% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, 0.6 weight% of a copolymer of vinyl pyrrolidone and vinyl acetate, 58.8 weight% of ethanol, and 40.0 weight% of liquefied petroleum gas.

[0091] Production Example 3: Production of the antiviral aerosol composition of the present invention (Part 3)

[0092] (Process 1)

[0093] In a 250 mL iBoy PP wide-mouth bottle, 4.4 g of the mesoporous silica doped with copper and aluminum obtained in Preparation Reference Example 1, 83.6 g of ethanol, 220 g of alumina balls were assembled on a ball mill stand at room temperature and processed at a rotation speed of 180 rpm for 8 hours, then the alumina balls were removed to obtain an ethanol slurry with a median particle size of about 0.5 μm and a mesoporous silica content of 5 wt% doped with copper and aluminum.

[0094] (Process 2)

[0095] The ethanol slurry with a median particle size of about 0.5 μm and a content of 5 wt% of mesoporous silica doped with copper and aluminum obtained in step 1, powder of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) and ethanol are mixed and stirred in a mass ratio of 20:1:79 to obtain a coating composition with a content of 1 wt% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, a content of 1 wt% of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 98 wt% of ethanol as a stock solution.

[0096] (Process 3)

[0097] The original liquid obtained in step 2 and liquefied petroleum gas as a propellant are filled into an aerosol can at a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention, which contains 0.6 weight% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, 0.6 weight% of a copolymer of vinyl pyrrolidone and vinyl acetate, 58.8 weight% of ethanol, and 40.0 weight% of liquefied petroleum gas.

[0098] Production Example 4: Production of the antiviral aerosol composition of the present invention (Part 4)

[0099] The same method as in Manufacturing Example 3 was followed, except that in step 2 of Manufacturing Example 3, the ethanol slurry containing 5 wt% of mesoporous silica doped with copper and aluminum and having a median particle size of about 0.5 μm obtained in step 1, the powder of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630), and ethanol were mixed in a mass ratio of 40:1:159, to obtain a coating composition containing 1 wt% of mesoporous silica doped with copper and aluminum and having a median particle size of about 0.5 μm, 0.5 wt% of a copolymer of vinyl pyrrolidone and vinyl acetate, and 98.5 wt% of ethanol as a stock solution. The obtained raw liquid and liquefied petroleum gas as a propellant are filled into an aerosol can at a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention having a content of 0.6 wt% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, a content of 0.3 wt% of a copolymer of vinyl pyrrolidone and vinyl acetate, a content of 59.1 wt% of ethanol, and a content of 40.0 wt% of liquefied petroleum gas.

[0100] Production Example 5: Production of the antiviral aerosol composition of the present invention (Part 5)

[0101] In a 2L iBoy PP wide-mouth bottle, 70 g of a 50 wt% aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA W735, manufactured by Ashland, ratio of vinyl pyrrolidone unit to vinyl acetate unit is 7:3, weight average molecular weight (nominal value) 27,300), 455 g of ethanol, 175 g of an ethanol slurry of 20 wt% mesoporous silica doped with copper and aluminum having a median particle size of about 0.6 μm obtained in step 1 of Preparation Example 1, 1760g of alumina balls were assembled on a ball mill stand at room temperature and processed at a speed of 500rpm for 9 hours, and then the alumina balls were removed to obtain a coating composition having a median particle size of about 0.5μm, a content of 5% by weight of mesoporous silica doped with copper and aluminum, a content of 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, a content of 5% by weight of water, and a content of 85% by weight of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution having a median particle size of about 0.5μm, a content of 1% by weight of mesoporous silica doped with copper and aluminum, a content of 1% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, a content of 1% by weight of water, and a content of 97% by weight of ethanol. The obtained raw liquid and liquefied petroleum gas as a propellant are filled into an aerosol can in a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention, which contains 0.6 weight% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, 0.6 weight% of a copolymer of vinyl pyrrolidone and vinyl acetate, 0.6 weight% of water, 58.2 weight% of ethanol, and 40.0 weight% of liquefied petroleum gas.

[0102] Production Example 6: Production of the antiviral aerosol composition of the present invention (Part 6)

[0103] The same method as in Preparation Example 5 was used except that a 50 wt % aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA W735) was used instead of a 50 wt % ethanol solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA E535, manufactured by Ashland, a ratio of vinyl pyrrolidone unit to vinyl acetate unit of 5:5, a weight average molecular weight (nominal value) of 36,700) to obtain a coating composition containing 5 wt % of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, 5 wt % of a copolymer of vinyl pyrrolidone and vinyl acetate, and 90 wt % of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution containing 1 wt % of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, 1 wt % of a copolymer of vinyl pyrrolidone and vinyl acetate, and 98 wt % of ethanol. The obtained raw liquid and liquefied petroleum gas as a propellant are filled into an aerosol can in a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention, which contains 0.6 weight% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, 0.6 weight% of a copolymer of vinyl pyrrolidone and vinyl acetate, 58.8 weight% of ethanol, and 40.0 weight% of liquefied petroleum gas.

[0104] Production Example 7: Production of the antiviral aerosol composition of the present invention (Part 7)

[0105] The same method as in Preparation Example 5 was used except that a 50 wt % aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA W735) was used instead of a 50 wt % ethanol solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA E335, manufactured by Ashland, a ratio of vinyl pyrrolidone unit to vinyl acetate unit of 3:7, a weight average molecular weight (nominal value) of 28,800) to obtain a coating composition having a content of 5 wt % of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, a content of 5 wt % of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90 wt % of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution having a content of 1 wt % of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, a content of 1 wt % of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 98 wt % of ethanol. The obtained raw liquid and liquefied petroleum gas as a propellant are filled into an aerosol can in a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention, which contains 0.6 weight% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, 0.6 weight% of a copolymer of vinyl pyrrolidone and vinyl acetate, 58.8 weight% of ethanol, and 40.0 weight% of liquefied petroleum gas.

[0106] Production Example 8: Production of the antiviral aerosol composition of the present invention (Part 8)

[0107] The same method as in Preparation Example 1 was followed except that polyvinyl pyrrolidone powder (PVP K15, manufactured by Ashland, weight average molecular weight (nominal value) 8,000) was used instead of the powder of the copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) to obtain a coating composition containing 5% by weight of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, 5% by weight of polyvinyl pyrrolidone, and 90% by weight of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution containing 1% by weight of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, 1% by weight of the copolymer of vinyl pyrrolidone and vinyl acetate, and 98% by weight of ethanol. The obtained raw liquid and liquefied petroleum gas as a propellant are filled into an aerosol can in a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention, which has a median particle size of about 0.5 μm, a content of mesoporous silica doped with copper and aluminum, a content of 0.6 weight%, a content of polyvinyl pyrrolidone, a content of 0.6 weight%, a content of ethanol, and a content of liquefied petroleum gas of 40.0 weight%.

[0108] Production Example 9: Production of the antiviral aerosol composition of the present invention (Part 9)

[0109] The same method as in Preparation Example 1 was followed except that polyvinyl pyrrolidone powder (PVP K30, manufactured by Ashland, Inc., weight average molecular weight (nominal value) 60,000) was used instead of powder of copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630), thereby obtaining a coating composition having a content of 5% by weight of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, a content of 5% by weight of polyvinyl pyrrolidone, and a content of 90% by weight of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution having a content of 1% by weight of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm, a content of 1% by weight of copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 98% by weight of ethanol. The obtained raw liquid and liquefied petroleum gas as a propellant are filled into an aerosol can in a weight ratio of 6:4, thereby obtaining an antiviral aerosol composition of the present invention, which has a median particle size of about 0.5 μm, a content of mesoporous silica doped with copper and aluminum, a content of 0.6 weight%, a content of polyvinyl pyrrolidone, a content of 0.6 weight%, a content of ethanol, and a content of liquefied petroleum gas of 40.0 weight%.

[0110] Test Example 1: Antiviral effect of the coating formed by the antiviral aerosol composition of the present invention on enveloped viruses

[0111] (1) Film formation by aerosol coating

[0112] The aerosol can filled with the antiviral aerosol composition of the present invention prepared in Manufacturing Example 1 was placed horizontally, and the entire surface of a 10 cm × 20 cm PET film was sprayed evenly from a height of 15 cm for 7 seconds (spraying amount 1.36 g / sec) and then dried naturally to form a coating on the surface of the PET film. It was also confirmed that when the antiviral aerosol composition of the present invention prepared in Manufacturing Example 1 was sprayed from the aerosol can, there was no spray failure caused by nozzle clogging, etc. The coating formed on the surface of the PET film was white, and the carrying capacity of the mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm was 0.27 mg / cm 2 It should be noted that the carrying capacity of mesoporous silica is calculated based on the amount of copper in the crucible measured by an inductively coupled plasma emission spectrometer after a PET film with a white coating formed on the surface is placed in a crucible and 6 mol / L hydrochloric acid is added and heated at 120°C for 1 hour.

[0113] (2) Evaluation of antiviral effects

[0114] MDCK cells (canine kidney-derived cells) as host cells were infected with influenza A virus (H3N2, A / Hong Kong / 8 / 68; TC adaptability, ATCC VR-1679), and the cell residues were removed by centrifugation after culture to obtain a virus suspension (infectious titer: 4.7×10 7 PFU / mL). According to ISO 21702, 0.4 mL of the virus suspension was dripped onto a 5 cm square test piece cut from a PET film with a white coating formed on the surface, covered with a 4 cm square film, and allowed to stand at 25°C. After 24 hours, a virus washing solution was applied to the test piece to wash away the virus, and the virus infection titer was measured by a plaque assay. The results are shown in Table 1. It should be noted that Table 1 also shows the results of the same test using the antiviral aerosol composition of the present invention prepared in Manufacturing Examples 5 to 7, as well as the results when the virus suspension was dripped onto a 5 cm square PET film as a control.

[0115] [Table 1]

[0116]

[0117] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0118] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0119] Mw: weight average molecular weight (nominal value)

[0120] Antiviral activity value [R] = [U t ]-[A t ]

[0121] As shown in Table 1, the coating films formed by the antiviral aerosol compositions of the present invention prepared in Production Examples 1 and 5 to 7 exhibited excellent antiviral effects on influenza viruses, which are enveloped viruses.

[0122] Test Example 2: Antiviral effect of the coating formed by the antiviral aerosol composition of the present invention on non-enveloped viruses

[0123] (1) Formation of coating film by aerosol coating

[0124] The antiviral aerosol composition of the present invention prepared in Production Example 1 was subjected to the same procedure as in Test Example 1 to form a white coating film on the surface of a 10 cm×20 cm PET film.

[0125] (2) Evaluation of antiviral effects

[0126] CRFK cells (feline kidney-derived cells) as host cells were infected with feline calicivirus (F-9, strain: F-9, ATCC VR-782), which was used as a substitute virus for norovirus. After culture, cell debris was removed by centrifugation to obtain a virus suspension (infectious titer: 2.4×10 7 PFU / mL). According to ISO 21702, 0.4 mL of the virus suspension was dripped onto a 5 cm square test piece cut from a PET film with a white coating formed on the surface, covered with a 4 cm square film, and allowed to stand at 25°C. After 24 hours, a virus washing solution was applied to the test piece to wash away the virus, and the virus infection titer was measured by a plaque assay. The results are shown in Table 2. It should be noted that Table 2 also shows the results of the same test using the antiviral aerosol composition of the present invention prepared in Manufacturing Examples 5 to 7, as well as the results when the virus suspension was dripped onto a 5 cm square PET film as a control.

[0127] [Table 2]

[0128]

[0129] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0130] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0131] Mw: weight average molecular weight (nominal value)

[0132] Antiviral activity value [R] = [U t ]-[A t ]

[0133] As shown in Table 2, the coating films formed by the antiviral aerosol compositions of the present invention prepared in Production Examples 1 and 5 to 7 exhibited excellent antiviral effects on feline calicivirus, which is a non-enveloped virus.

[0134] Test Example 3: Adsorption of hemagglutinin (HA) by the coating formed by the antiviral aerosol composition of the present invention

[0135] The adsorption of HA, a surface protein of influenza virus, to the coating film formed by the antiviral aerosol composition of the present invention was evaluated using the HA (H1N1) (A / California / 06 / 2009 hemagglutinin ELISA development kit (Immune Technology IT-E3Ag-2009H1N1-California / 06). Specifically, the antiviral aerosol composition of the present invention prepared in Preparation Example 1 was used in the same manner as in Test Example 1. A PET film having a white coating film of 10 cm×20 cm on the surface was cut out to obtain an area of ​​7.4 cm2 The test piece (2 mg of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm) was immersed in 2 mL of HA solution with an initial concentration of 25.3 ng / mL, stirred for 20 seconds using a vortex mixer, and allowed to stand at room temperature. After 3 minutes, the film was removed, and then centrifuged to settle the solid components. The supernatant was collected and its HA concentration was measured. The adsorption rate relative to HA was calculated according to the formula: Adsorption rate (%) = ((HA initial concentration - HA concentration after 3 minutes) / HA initial concentration) × 100. 2 mg of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm was added to 2 mL of HA solution with an initial concentration of 25.3 ng / mL. When the adsorption rate of mesoporous silica for HA calculated based on the same method as above was taken as 100, the relative values ​​of the adsorption rate for HA calculated in the test example are shown in Table 3. It should be noted that Table 3 also shows the results of the same test using the antiviral aerosol compositions of the present invention prepared in Preparation Examples 8 and 9.

[0136] [Table 3]

[0137]

[0138] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0139] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0140] PVP: Polyvinylpyrrolidone

[0141] Mw: weight average molecular weight (nominal value)

[0142] As shown in Table 3, the adsorption rate of the coating formed by the antiviral aerosol composition of the present invention prepared in Example 1 relative to HA is almost the same as the adsorption rate of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm for HA, and the coexistence of the copolymer of vinyl pyrrolidone and vinyl acetate in the coating almost does not lead to a decrease in the adsorption rate of mesoporous silica for HA. Therefore, it can be confirmed that the coating formed by the antiviral aerosol composition of the present invention prepared in Example 1 has an excellent adsorption effect on HA. Although it is confirmed that the coating formed by the antiviral aerosol composition of the present invention prepared in Examples 8 and 9 also has an excellent adsorption effect on HA, it is also found that there is a trend that the effect weakens as the weight average molecular weight of polyvinyl pyrrolidone increases.

[0143] Test Example 4: Durability of the coating formed by the antiviral aerosol composition of the present invention

[0144] The aerosol can filled with the antiviral aerosol composition of the present invention prepared in Manufacturing Example 1 was placed horizontally, sprayed onto the PET film from a height of 15 cm for 1 second and dried naturally, and two test pieces (test piece A and test piece B) of 2 cm × 4 cm were cut out from the PET film with a white coating of about 6 cm in diameter formed on the surface. The entire surface of the coating of test piece A was pressed by hand. (Registered trademark, the same below) The tape is peeled off immediately after being firmly attached. The tape-covered test pieces A and B were placed in crucibles, 6 mol / L hydrochloric acid was added and heated at 120°C for 1 hour. The amount of copper in the crucible was measured using an inductively coupled plasma emission spectrometer, and the results were respectively The copper content of test piece A and test piece B after the tape is peeled off. The durability of the coating was evaluated. The results are shown in Table 4. It should be noted that Table 4 also shows the results of the same test using the antiviral aerosol composition of the present invention prepared in Manufacturing Examples 4 and 5, and the results of the same test using a stock solution of 1% by weight of mesoporous silica doped with copper and aluminum having a median particle size of about 0.5 μm and 99% by weight of ethanol in an aerosol can filled with liquefied petroleum gas as a propellant at a weight ratio of 6:4 as a control.

[0145] [Table 4]

[0146]

[0147] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0148] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0149] Mw: weight average molecular weight (nominal value)

[0150] As shown in Table 4, by using a polymer containing a vinyl pyrrolidone unit as the resin component of the aerosol composition, a coating film that can be firmly maintained can be formed on the surface of the PET film by aerosol coating.

[0151] Test Example 5: Spray adhesion of the antiviral aerosol composition of the present invention

[0152] When the aerosol composition is sprayed onto the surface of the object, part of the stock solution is lifted from the surface of the object due to the strong airflow, resulting in the phenomenon of failure to adhere and scattering. Therefore, the spray adhesion of the aerosol composition can be evaluated based on the formula: Spray adhesion rate (%) = (actual coating amount of stock solution per unit area / theoretical coating amount of stock solution per unit area) × 100. Among them, the actual coating amount of the stock solution per unit area is calculated by dividing the amount of attachment on the surface of the object immediately after the aerosol composition is sprayed by the coating area, and the theoretical coating amount of the stock solution per unit area is calculated by dividing the theoretical coating amount of the stock solution by the coating area. The theoretical coating amount of the stock solution is calculated based on the formula: (amount of aerosol composition before spraying - amount of aerosol composition after spraying) × the ratio of the stock solution of the aerosol composition. According to this method, the spray adhesion of the antiviral aerosol composition of the present invention prepared in Manufacturing Example 1 after the coating film was formed in Test Example 4 was evaluated. The results are shown in Table 5. Table 5 also shows the results of the same test using the antiviral aerosol composition of the present invention prepared in Manufacturing Examples 4 and 5, as well as the results of the same test using a stock aerosol composition as a control, which contains 1% by weight of mesoporous silica doped with copper and aluminum and has a median particle size of about 0.5 μm and an ethanol content of 99% by weight, and liquefied petroleum gas as a propellant, and is filled into an aerosol can in a weight ratio of 6:4.

[0153] [Table 5]

[0154]

[0155] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0156] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0157] Mw: weight average molecular weight (nominal value)

[0158] It can be seen from Table 5 that the spray adhesion rate of the aerosol composition can be improved by using a polymer containing a vinyl pyrrolidone unit as the resin component of the aerosol composition. Taking the results of Test Example 5 into consideration together with the results of Test Example 4, it can be seen that the antiviral aerosol composition of the present invention can form a coating film that can be firmly maintained on the surface of the PET film at a high spray adhesion rate through aerosol coating.

[0159] Test Example 6: Stability of the antiviral aerosol composition of the present invention

[0160] 20 g of each antiviral aerosol composition of the present invention prepared in Manufacturing Examples 1 to 9 was filled into a 100 mL pressure-resistant glass bottle, the appearance was observed, and the following five items were studied. The results showed that all antiviral aerosol compositions of the present invention had no problems affecting practical use in all items and had high stability.

[0161] ·Whether the stock solution components other than mesoporous silica are miscible with liquefied petroleum gas.

[0162] Whether precipitates are generated

[0163] ·Whether the composition changes color due to the dissolution of copper, aluminum, etc.

[0164] Can the precipitated mesoporous silica be redispersed by oscillation?

[0165] Does mesoporous silica aggregate?

[0166] The composition of the antiviral aerosol composition of the present invention prepared in Example 1 was changed, the content of mesoporous silica was increased to 3 wt% (the ethanol content should be increased to reduce the content), the content of the copolymer of vinyl pyrrolidone and vinyl acetate was increased to 3 wt% (the ethanol content should be increased to reduce the content), the ethanol content was reduced to 40 wt% (the liquefied petroleum gas content should be reduced to reduce the content), the ethanol content was increased to 90 wt% (the liquefied petroleum gas content should be increased to reduce the content), the liquefied petroleum gas content was reduced to 10 wt% (the ethanol content should be reduced to reduce the content), the liquefied petroleum gas content was increased to 60 wt% (the ethanol content should be increased to reduce the content), the liquefied petroleum gas was changed to hydrofluoroolefin (such as HFO-1234ze), or nitrogen and carbon dioxide were mixed in the liquefied petroleum gas, but there was no significant difference in the evaluation of stability. Moreover, even if ethanol (58.8 wt%) was changed to ethanol (10.8 wt%) + water (48.0 wt%), and liquefied petroleum gas was changed to dimethyl ether, there was no significant difference in the evaluation of stability. Even when the antiviral aerosol composition of the present invention prepared in Preparation Example 9 was subjected to the same compositional changes as those made to the antiviral aerosol composition of the present invention prepared in Preparation Example 1, there was no significant difference in the evaluation of stability.

[0167] However, when the copolymer of vinyl pyrrolidone and vinyl acetate in the antiviral aerosol composition of the present invention prepared in Production Example 1 is changed to any one of ethyl cellulose (Antaron ECo ethyl cellulose, manufactured by Ashland), (octylacrylamide / hydroxypropyl acrylate / butylaminoethyl methacrylate) copolymer (AMPHOMER, manufactured by Nouryon), diisostearyl polyglyceryl-3-dilinoleate, (caprylic acid / capric acid) triglyceride (SolAmaze, manufactured by Nouryon), and polyquaternium-51 (LIPIDURE-PMB, manufactured by NOF Corporation) known as a resin component of the aerosol composition, it was confirmed after studying the above five items that any aerosol composition had practical problems in at least one item and had poor stability.

[0168] Manufacturing Reference Example 2: Manufacturing of Non-porous Silica Doped with Copper and Aluminum

[0169] A solution (a) formed by dissolving sodium silicate (sodium metasilicate (nonahydrated salt): manufactured by Nippon Chemical Industry Co., Ltd., SiO2 / Na2O=0.9-1.1 (manufacturer's nominal value)) as a raw material for silica in water as a solvent, and a solution (b) formed by dissolving copper chloride as a raw material for doping copper into non-porous silica and aluminum chloride as a raw material for doping aluminum into non-porous silica in water as a solvent were prepared separately. After mixing and stirring the solution (a) and the solution (b) at room temperature for 5 minutes, hydrochloric acid was further added dropwise for 30 minutes under stirring (the pH value at the beginning of the addition of hydrochloric acid was 14, and the pH value at the end was 9). After about 30 minutes, the generated precipitate was filtered by suction, and the filtered precipitate was thoroughly washed with water (until the conductivity of the washing liquid was less than 1000μS), and then dried at 80°C overnight. The recovered filter cake was coarsely ground with a mixer and then fired at 570° C. for 5 hours, thereby obtaining the target product, non-porous silica doped with copper and aluminum, as a slightly bluish white powder.

[0170] It should be noted that the amounts of copper chloride as a raw material for doping copper into non-porous silica, aluminum chloride as a raw material for doping aluminum into non-porous silica, and water as a solvent relative to 1 mol of sodium silicate as a raw material for silica are as follows:

[0171] Copper chloride: 0.0201 mol

[0172] Aluminum chloride: 0.0475 mol

[0173] Solution (a) Preparation Water: 48.6 mol

[0174] Solution (b) Preparation Water: 90.2 mol

[0175] Furthermore, 1.59 mol of hydrochloric acid was used per 1 mol of sodium silicate as a raw material of silica.

[0176] The BET specific surface area of ​​the non-porous silica doped with copper and aluminum obtained by the above method is 18.8 m 2 / g. In addition, the copper content in the non-porous silica doped with copper and aluminum was 1.43 wt%, and the aluminum content was 2.03 wt%. The doping of copper and aluminum in the non-porous silica was confirmed by X-ray photoelectron spectroscopy and transmission electron microscopy.

[0177] Production Example 10: Production of the antiviral aerosol composition of the present invention (Part 10)

[0178] The same method as in Manufacturing Example 1 was used except that the non-porous silica doped with copper and aluminum obtained in Manufacturing Reference Example 2 was used instead of the mesoporous silica doped with copper and aluminum obtained in Manufacturing Reference Example 1 to obtain a coating composition containing 5% by weight of non-porous silica doped with copper and aluminum having a median particle size of about 0.5 μm, 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and 90% by weight of ethanol. The obtained coating composition was mixed with ethanol at a weight ratio of 1:4 to obtain a stock solution containing 1% by weight of non-porous silica doped with copper and aluminum, 1% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and 98% by weight of ethanol. The obtained stock solution and liquefied petroleum gas as a propellant were filled into an aerosol can in a weight ratio of 6:4, and an antiviral aerosol composition of the present invention having a non-porous silica content of 0.6% by weight doped with copper and aluminum, a copolymer of vinyl pyrrolidone and vinyl acetate of 0.6% by weight, an ethanol content of 58.8% by weight, and a liquefied petroleum gas content of 40.0% by weight was obtained. The antiviral aerosol composition of the present invention has the same spray adhesion and stability as the antiviral aerosol composition of the present invention prepared in Manufacturing Example 1. Moreover, the coating formed by the antiviral aerosol composition of the present invention has the same antiviral effect and durability as the coating formed by the antiviral aerosol composition of the present invention prepared in Manufacturing Example 1.

[0179] Industrial Applicability

[0180] The present invention has industrial applicability because it can provide an antiviral aerosol composition that can form a coating film that exhibits excellent antiviral performance of copper-doped silica and is firmly maintained on the surface of an article, has high stability, can apply an aerosol without clogging the nozzle, a coating film formed by the antiviral aerosol composition, and an article having the coating film.

Claims

1. An antiviral aerosol composition, characterized in that: contain: (1) Copper doped silicon dioxide; (2) Polymers containing vinyl pyrrolidone units; (3) an alcohol solvent or a mixed solvent of an alcohol solvent and water; and (4) Propellant.

2. The antiviral aerosol composition according to claim 1, characterized in that The silicon dioxide is also doped with aluminum.

3. The antiviral aerosol composition according to claim 1, characterized in that The silicon dioxide is porous silicon dioxide.

4. The antiviral aerosol composition according to claim 1, characterized in that The polymer containing a pyrrolidone unit is a copolymer of a vinyl pyrrolidone unit and a unit other than vinyl pyrrolidone.

5. The antiviral aerosol composition according to claim 4, characterized in that The ratio of the vinyl pyrrolidone unit to the unit other than vinyl pyrrolidone (vinyl pyrrolidone unit:unit other than vinyl pyrrolidone) is 2:8 to 8:

2.

6. The antiviral aerosol composition according to claim 4, characterized in that The copolymer of a vinyl pyrrolidone unit and a unit other than vinyl pyrrolidone is a copolymer of vinyl pyrrolidone and vinyl acetate.

7. The antiviral aerosol composition according to claim 1, characterized in that The polymer containing pyrrolidone units is polyvinylpyrrolidone.

8. The antiviral aerosol composition according to claim 1, characterized in that The weight average molecular weight of the polymer containing the pyrrolidone unit is 5,000 to 1,500,000.

9. The antiviral aerosol composition according to claim 1, characterized in that The alcohol solvent is ethanol.

10. The antiviral aerosol composition according to claim 1, characterized in that The propellant is at least one selected from liquefied petroleum gas, nitrogen, carbon dioxide, dimethyl ether, hydrofluoroolefins, and hydrofluorocarbons.

11. The antiviral aerosol composition according to claim 1, characterized in that The contents of copper-doped silica, polymer containing vinyl pyrrolidone units, alcoholic solvent or a mixed solvent of an alcoholic solvent and water, and propellant in the antiviral aerosol composition are as follows: the content of copper-doped silica is 0.1 to 5% by weight, the content of polymer containing vinyl pyrrolidone units is 0.1 to 5% by weight, the content of alcoholic solvent or a mixed solvent of an alcoholic solvent and water is 30 to 90% by weight, and the content of propellant is 5 to 65% by weight.

12. The antiviral aerosol composition according to claim 1, characterized in that The weight ratio of copper-doped silica to the polymer containing vinyl pyrrolidone units (copper-doped silica: polymer containing vinyl pyrrolidone units) is 5:95 to 75:

25.

13. A method for producing an antiviral aerosol composition, characterized in that: Include: The step of placing the following (1) to (3) in a processing container and mixing the stock solution obtained by the preparation method including the step of ball milling with (4) a propellant, (1) Copper-doped silicon dioxide, (2) a polymer containing a vinyl pyrrolidone unit, and (3) An alcohol solvent or a mixed solvent of an alcohol solvent and water.

14. A coating film, characterized in that: It is formed from the antiviral aerosol composition according to claim 1.

15. An article, characterized in that A coating film according to claim 11.

Citation Information

Patent Citations

  • Porous silica, deodorant, and method for producing deodorant

    JP2020015640A

  • Antimicrobial and antiviral composition, and method of producing the same

    CN104837347A

  • Inorganic antiviral agent

    JP2021175741A